A note on Marx - Finn Olesen; Frank Jensen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2001)
Throughout all his life Karl Marx wrote angrily about capitalism. By use of a dialectic approach he was convinced that the working class had to unite and make a social revolution and thereby free them selves from exploitation. Marx himself was in many ways a dialectic person as we try to show in the note. So in some sense he became one with his scientific methodology.
Keywords: B14; B31; 330